Momentum: a practical solution to calculate the optimal load for resisted sled sprint training - Tierney, P.; Reardon, C.; Delahunt, E. (Sport Performance & Science Reports, 2019)
Currently, there is a lack of consensus regarding the optimal load with which to expose athletes to during resisted sled sprint training for the purpose of training linear acceleration and sprint performance. We propose that the use of "momentum" is a practical method of determining the optimal load for resisted sled sprint training.